Time-Lag in Feeding Schedule Acts as a Stressor That Alters Circadian Oscillators in Goldfish - Gómez-Boronat, Miguel; Sáiz, Nuria; Delgado, María J.; de Pedro, Nuria; Isorna, Esther (Frontiers in Physiology, 2018)
The circadian system controls temporal homeostasis in all vertebrates. The light-dark cycle is the most important zeitgeber (“time giver”) of circadian system, but feeding time also acts as a potent synchronizer in the functional organization of the teleost circadian system. In mammals is well known that food intake during the rest phase promotes circadian desynchrony which has been associated with metabolic diseases. However, the impact of a misalignment of light-dark and feeding cycles in the entrainment of fish circadian oscillators is largely unknown. The objective of this work was to investigate how a time-lag feeding alters temporal homeostasis and if this could be considered a stressor. To this aim, goldfish maintained under a 12 h light-12 h darkness were fed at mid-photophase (SF6) or mid-scotophase (SF18). Daily rhythms of locomotor activity, clock genes expression in hypothalamus, liver and head kidney, and circulating cortisol were studied. Results showed that SF6 fish showed daily rhythms of bmal1a and clock1a in all studied tissues, being in antiphase with rhythms of per1 genes, as expected for proper functioning clocks. The 12-h shift in scheduled feeding induced a short phase advance (4-5-h) of the clock genes daily rhythms in the hypothalamus, while in the liver the shift for clock genes expression rhythms was the same that the feeding time shift ( 12 h). In head kidney, acrophases of per genes underwent a 12-h shift in SF18 animals, but only 6 h shift for clock1a. Plasma cortisol levels showed a significant daily rhythm in animals fed at SF6, but not in SF18 fish fed, which displayed higher cortisol values throughout the 24-h. Altogether, results indicate that hypothalamus, liver and head kidney oscillate in phase in SF6 fish, but these clocks are desynchronized in SF18 fish, which could explain cortisol alterations. These data reinforce the hypothesis that the misalignment of external cues (daily photocycle and feeding time) alters fish temporal homeostasis and it might be considered a stressor for the animals.